Intention to adopt mobile payment in physical stores: Individual switching behavior perspective based on Push–Pull–Mooring (PPM) theory. Issue 2 (26th November 2019) - Handarkho, Yonathan Dri; Harjoseputro, Yulius
Abstract : Purpose: The purpose of this paper is to develop a theoretical model based on Push–Pull–Mooring (PPM) framework consisting of direct, indirect and moderating effects, derived from technology acceptance model, unified theory of acceptance and use of technology and other extended theory, to address the main factor influencing an individual in adopting mobile payment (MP) in physical stores. The research, therefore, utilized individual switching behavior as an underpinning to explain MP adoption in an offline context. Design/methodology/approach: The theoretical model was tested by collecting data from 459 respondents in Indonesia through online self-administered questionnaires. Findings: The finding indicated consumer innovativeness has the most influential direct effect on MP adoption, followed by deal proneness, perceived convenience and perceived herd behavior. Meanwhile, perceived enjoyment and subjective norms were found to have an indirect effect on the adaptation of MP through mediator convenience. Furthermore, age, gender, occupation and income did not have any moderating effect for all the direct influence of MP adoption. Originality/value: Previous literature only focused on direct intention. However, this study observed the adoption of MP in a physical store by involving the switching behavior. It specifically puts concern and objective as the factors that influence user intention to switch from their old payment system to the MP system in bricks and mortar store using PPM framework.